The Linkage of Human and Money Flows to Rural-Urban Fringe Poverty in South Sumatra, Indonesia: In an Islamic Perspective - Yuliana, Sa’adah; Yunisvita, Yunisvita; Yulianita, Anna; Muhyiddin, Nurlina T.; Bashir, Abdul (International Journal of Economics and Financial Issues, 2017)
The economic activity between regions as economic activities between villages and cities will lead to a flow of people and money. Interaction zone town village includes Rural Urban Fringe (RUF). Migration, of transport, and telecommunications as a form of interaction will have a positive meaning if they can be a means or efforts to eradicate poverty.The Islamic view of poverty is closely related to the teaching of Islam on various aspects of Islamic life order outlined in the Quran and Hadith. Poverty is an integral part of an assessment of the economic system in Islam which includes treasures, trading, buying and selling, justice, wealth, poverty and its causes and consequences, and ways to overcome them. This study aimed to analyze the relationship flow of people and money against poverty in the Rural Urban Fringe in South Sumatra province viewed from the perspective of Islam.This research was conducted in the city of South Sumatra, Prabumulih which is an area Rural Urban Fringe (RUF) by the number of respondents as many as 200 people. The results showed that the relatif size of income of rural communities, indicating that their interaction does not guarantee high rural-urban income will be accepted. However, their understanding of religion is good enough in the form of distribution of zakat al-fitr and zakat mal then it will be able to reduce poverty. The flow of goods and the flow of money has not had an impact on poverty reduction, but the distribution of zakat by the respondents indicated their poverty reduction solutions. Keywords: Flow of people; flow of money; poverty; rural urban fringe; zakat JEL Classifications: O15; R23